2007
DOI: 10.1038/ni1481
|View full text |Cite
|
Sign up to set email alerts
|

Essential function for SWI-SNF chromatin-remodeling complexes in the promoter-directed assembly of Tcrb genes

Abstract: The assembly of genes encoding antigen receptors is regulated by developmental changes in chromatin that either permit or deny access to a single variable-(diversity)-joining recombinase. These changes are guided by transcriptional promoters and enhancers, which serve as accessibility-control elements in antigen-receptor loci. The function of each accessibility-control element and the factors they recruit to remodel chromatin remain obscure. Here we show that the recruitment of SWI-SNF chromatin-remodeling com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 51 publications
5
57
0
Order By: Relevance
“…A highly flexible structure is consistent with reported extensive remodeling of chromatin at this genomic region during rearrangement, by protein factors such as switch/sucrose nonfermentable protein complex (SWI/SNF) (27) and high-mobility group proteins (HMG) (28). The latter protein had been shown to decrease greatly the persistence length of naked DNA, from ∼50 nm to only ∼5 nm (29).…”
Section: Mechanical Model Of Chromatin Explains Observed Biases In Jβ-dβsupporting
confidence: 58%
See 1 more Smart Citation
“…A highly flexible structure is consistent with reported extensive remodeling of chromatin at this genomic region during rearrangement, by protein factors such as switch/sucrose nonfermentable protein complex (SWI/SNF) (27) and high-mobility group proteins (HMG) (28). The latter protein had been shown to decrease greatly the persistence length of naked DNA, from ∼50 nm to only ∼5 nm (29).…”
Section: Mechanical Model Of Chromatin Explains Observed Biases In Jβ-dβsupporting
confidence: 58%
“…The ability of chromatin conformation to explain rearrangement frequencies at these other receptor loci will depend on the magnitude of the contributions from other factors (1,23,24,27,28,(34)(35)(36)(37) that influence the rearrangement process. In particular, the demonstrated effect of chromatin conformation on gene segment use is potentially further modulated by cis-acting elements such as RSSs (1,23,24,34), coding ends of genes (35), Vβ/Dβ promoters (34), and other molecular factors that regulate the accessibility of individual genes to enzymes involved in VDJ rearrangement (27,28,36,37). Additionally, gene segment use may be further modulated by thymic selection, homeostatic T-cell expansion in peripheral lymphoid organs, and clonal expansion during specific immune responses (38).…”
Section: Discussionmentioning
confidence: 99%
“…BRG1 stimulates in vitro recombination of chromatin and is also bound to regions in the T-cell receptor (TCR) and immunoglobulin loci that take part in recombination events (Golding et al, 1999;Kwon et al, 2000;Spicuglia et al, 2002;Morshead et al, 2003;Patenge et al, 2004). More recent studies have shown SWI/SNF to be fundamental to the promoter-directed assembly of TCR-b (TCRB) genes (Osipovich et al, 2007); SWI/ SNF is recruited to promoters and then facilitates recombination by exposing segments of genomic DNA to V(D)J recombinase. The fact that loss of this chromatin-remodeling complex in thymocytes inactivates recombinase targets at the endogenous TCRB locus (Osipovich et al, 2007) provides further evidence for the role of SWI/SNF in recombination.…”
Section: Brm and Brg1 Control The Expression Of Genes That Are Involvmentioning
confidence: 99%
“…More recent studies have shown SWI/SNF to be fundamental to the promoter-directed assembly of TCR-b (TCRB) genes (Osipovich et al, 2007); SWI/ SNF is recruited to promoters and then facilitates recombination by exposing segments of genomic DNA to V(D)J recombinase. The fact that loss of this chromatin-remodeling complex in thymocytes inactivates recombinase targets at the endogenous TCRB locus (Osipovich et al, 2007) provides further evidence for the role of SWI/SNF in recombination.…”
Section: Brm and Brg1 Control The Expression Of Genes That Are Involvmentioning
confidence: 99%
“…SWI/SNF CRCs are important for controlling differentiation and proliferation in many cell types. In lymphocytes, CRCs have been implicated in activating transcription and antigen receptor rearrangements (8)(9)(10).…”
Section: T He Development Of B Cells From Progenitor Cells In the Bonementioning
confidence: 99%